Estimation of Average of Global Solar Radiation Depending on Sunshine Duration Hours for Iraqi Metrological Stations - abd, Mertah naji; Al-Hassany, Gheidaa Sabeeh (Iraqi Journal of Science, 2019)
In this study, the global solar radiation for the locations of fourteen Iraqi metrological stations was studied and calculated. This was performed because most of the Iraqi stations lack solar radiation measuring devices. The equation postulated by Angström (1924) and modified by Prescott (1940) was utilized for the estimation of the solar radiation for the fourteen Iraqi metrological stations depending on sunshine duration measurements of these stations. Empirical constants of Angstrom-Prescott equation that are adopted by the Food and Agriculture Organization (FAO) were used for obtaining the results. The utilized data reported in this study were taken from the Republic of Iraq Meteorological Office (RIMO). The calculations and diagrams were carried out and the results were obtained by making advantage of Excel's program capabilities.